Artificial Intelligence and Human Existence: An Intellectual Reading in Economic Dimensions (قضايا سياسية, 2024)
Artificial intelligence is one of the modern sciences that has been linked to humans since the past decades, making politics an integral part of society, as it contains human life. This is what encouraged us to commit to the new design in thinking about how to employ it for their higher service to the economy and the economy, regardless of the persistence in thinking about their organization of nascent artificial intelligence, or the development of electronics to legislate religious laws, and laws that take into account the constitutions of countries. So some liberal AI programs started as a platform for illegal content, and were partially disrupted by the economic impact of the country, without wishing projects in steps to prevent the use of their mass.The countries sponsoring major artificial intelligence companies have been keen to limit the regulation of the development of economic innovation, claiming that this restricts the freedom to develop technological thinking. Therefore, today all countries of the world face fears and harmful repercussions on their societies from the humanitarian, economic, political, media, and even health aspects..., which contributes to changing many individuals’ behaviors and thoughts, leading to a world that generates nonsense, especially after the failure of the capabilities to control it, to become some future versions of Applications threaten humanity rather than serve it. The source and starting point of artificial intelligence is the human mind, but the way humans think is different from the way artificial intelligence thinks and works.Therefore, the countries of the world are seriously thinking today that they are on the cusp of a global threat that has no limits or restrictions, and they have no choice but to stand up to it by holding international conferences, exchanging ideas through dialogue, listening to dissenting viewpoints, establishing international rules and laws, and treaties guaranteeing the national interests of countries, and reaching agreement. Which regulates economic innovation, to reach a common formula through which the management, regulation and control of artificial intelligence is placed under a common international authority, not under the authority of the private companies sponsoring and operating economic artificial intelligence.